HUBUNGAN PENDIDIKAN KESEHATAN DENGAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG FLOUR ALBUS DI DESA TANGUNAN KECAMATAN PURI KABUPATEN MOJOKERTO - Sari Priyanti; Wiwit Sulistyawati; Agustin Dwi Syalfina; Dian Irawati (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Flour Albus is a white fluid that comes out of the burrow excessively. Flour Albus can be divided into several types, including normal (physiological) and abnormal (pathological). Based on data from (BKKBN) in 2012, that, women in Indonesia experience flour albus as much as 75%. These women had experienced fluor albus at least once in their lives and 45% of them had experienced fluor albus 2 or more occurrences of flour albus. The purpose of this study was to determine how the relationship between health education and WUS knowledge about flour albus in Tangunan Village, Puri District, Mojokerto Regency.Methods This study used an analytic observational design with a cross sectional approach. The dependent variable was health education and the independent variable was WUS knowledge about Flour albus. The study was conducted in Tangunan Village, Puri District, Mojokerto Regency. This study conducted measurements by distributing questionnaires. The sample of this study was all WUS who attended health education activities about flour albus totaling 34 people. Data analysis is univariate and bivariate analysis.Based on the results of the study, the majority of respondents who received health education and good knowledge were as many as 14 respondents (41.2%). The results of the Fisher Exact test with a significance level of 0.05 obtained a significance value of 0.006, so the value of 0.006 <0.05 means that there is a relationship between health education and WUS knowledge about Flour albus.Suggestions for the community, especially WUS, should always increase knowledge in the health sector, especially reproductive health, health education can be used to increase one's knowledge, so health workers can always continuously provide scheduled health education to the community.